2015
DOI: 10.1016/j.stemcr.2014.12.006
|View full text |Cite|
|
Sign up to set email alerts
|

EZH2 Protects Glioma Stem Cells from Radiation-Induced Cell Death in a MELK/FOXM1-Dependent Manner

Abstract: SummaryGlioblastoma (GBM)-derived tumorigenic stem-like cells (GSCs) may play a key role in therapy resistance. Previously, we reported that the mitotic kinase MELK binds and phosphorylates the oncogenic transcription factor FOXM1 in GSCs. Here, we demonstrate that the catalytic subunit of Polycomb repressive complex 2, EZH2, is targeted by the MELK-FOXM1 complex, which in turn promotes resistance to radiation in GSCs. Clinically, EZH2 and MELK are coexpressed in GBM and significantly induced in postirradiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
142
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(150 citation statements)
references
References 38 publications
(65 reference statements)
5
142
1
2
Order By: Relevance
“…In a previous study, we demonstrated that the radioresistance of GBM tumors depends on MELK-mediated EZH2 signaling in GSCs (24). The MELK kinase inhibitor OTS167 is currently being tested in a phase I clinical trial for solid nonbrain cancers (https://clinicaltrials.gov/ct2/show/NCT01910545?term= OTS167&rank=1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we demonstrated that the radioresistance of GBM tumors depends on MELK-mediated EZH2 signaling in GSCs (24). The MELK kinase inhibitor OTS167 is currently being tested in a phase I clinical trial for solid nonbrain cancers (https://clinicaltrials.gov/ct2/show/NCT01910545?term= OTS167&rank=1).…”
Section: Resultsmentioning
confidence: 99%
“…We also found that EZH2-mediated GSC maintenance and the radiation resistance of GSCs depend on maternal embryonic leucine zipper kinase (MELK) by its protein complex formation with the transcription factor FOXM1 (24). These studies led us to speculate that the MELK/EZH2/STAT3 signaling axis is a central regulator for GSC tumorigenicity in GBM.…”
Section: Introductionmentioning
confidence: 84%
“…The addition of TMZ to radiation has increased median survival by several months (Stupp et al 2009), but lineage tracing studies in mouse models demonstrate that CSCs repopulate brain tumors after TMZ treatment . A number of molecular mechanisms have been identified that mediate the therapeutic resistance of CSCs to cytotoxic therapies, including the DNA damage checkpoint, Notch, NF-κB, EZH2, and PARP (Bao et al 2006a;Wang et al 2010;Bhat et al 2013;Venere et al 2014;Kim et al 2015), which suggests that CSCs develop multiple mechanisms of resistance that may require combinations of targeted agents. Moving forward, these studies demonstrate the importance of understanding the molecular alterations that are present in recurrent tumors and how these influence the structure of cells within the tumor hierarchy.…”
Section: Therapeutic Resistancementioning
confidence: 99%
“…In terms of glioblastoma, inactivated ALKBH5 inhibited the proliferation and tumorigenesis of GSCs and impaired GSCs self‐renewal 75. It is widely accepted that FOXM1 plays a pivotal role in regulating GSCs proliferation and self‐renewal 76, 77. ALKBH5 was found to demethylate FOXM1 nascent transcripts and promote FOXM1 expression, whereas long non‐coding RNA antisense of FOXM1 further promoted the interaction of FOXM1 nascent transcripts with ALKBH5.…”
Section: The Dual Role Of M6a Modification In Human Cancersmentioning
confidence: 99%